تأثير التسميد العضوي في بعض الصفات المورفولوجية والفزيولوجية لنبات الكزبرة Coriandrum sativum L. (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
The research was conducted during the agricultural season 2016 in the Syrian coast in Tartous province to study the effect of organic and mineral fertilization on earliness (germination, branching, full maturity) and some morphological (Plant height, number of branches, number of leaves) and physiological (Leaves surface area, Leaves area guide) characteristics of coriander (Coriandrum sativum L.). Five fertilizer coefficients were used:  The first coefficient (T1): Controle without fertilization, the second coefficient (T2): Chemical fertilization according to the fertilizer formula (K 60, P 120, N 80) kg / ha, the third coefficient (T3): Organic fertilizer 20 tons / ha, the fourth coefficient (T4): Organic fertilizer 30 tons / ha,  the fifth coefficient (T5): Mixed fertilization (organic 15 t / ha, chemical K3O, P6O, N4O kg / ha). The experiment was designed in the way of full random sectors in three replicates, where the results have revealed the surpassing of the combined fertilization (organic and chemical) (T5) on the Witness (T1) and chemical fertilization (T2) in reducing the number of days required for each stage of growth (germination, branching, flowering, physiological maturity, full maturity), plant height (cm), number of branches, number of leaves, leaf surface (cm2/ plant), dry matter weight (g / plant), relative growth rate (RGR / g /g/ week) and crop growth rate (CGR g / m2 / week). The organic fertilization 30 tons / ha (T5) surpassed the chemical fertilization (T2) in reducing the number of days required for growth and full maturity, plant height (cm), number of leaves/ plant, leaf surface (cm2/ plant), dry matter weight (g / plant). The results have revealed no Significant differences between the coefficient (T4) and the coefficient (T5) for most studied characteristics. نفذ البحث خلال الموسم الزراعي 2016 م في الساحل السوري في محافظة طرطوس قرية بيت الشيخ يونس لدراسة تأثير التسميد العضوي والمعدني في التبكير (الإنبات ،التفرع ،النضج التام) وبعض الصفات المورفولوجية (ارتفاع النبات,عدد الفروع،عدد الأوراق) والفزيولوجية (مساحة المسطح الورقي, دليل المساحة الورقية) لنبات الكزبرة (Coriandrum sativum L). استخدمت خمس معاملات سمادية (المعاملة الأولى (T1) شاهد من دون تسميد،المعاملة الثانية (T2) تسميد كيميائي وفق المعادلة السمادية (  K 60 , P 120 , N 80) كغ/هـ،المعاملة الثالثة (T3) تسميد عضوي  20 طن/هـ،المعاملة الرابعة (T4) تسميد عضوي 30طن/هـ، المعاملة الخامسة (T5) تسميد مختلط ( عضوي  15طن/هـ  , كيميائيK3O ,  P6O, N4O كغ/هـ). صممت التجربة بطريقة القطاعات العشوائية الكاملة في ثلاثة مكررات ، بينت النتائج تفوق التسميد المختلط (العضوي والكيميائي) (T5) على الشاهد (T1) والتسميد الكيميائي(T2) في تقليل عدد الأيام اللازمة لكل مرحلة من مراحل النمو(الإنبات ،التفرع ،الإزهار ،النضج الفسيولوجي،النضج التام) ،ارتفاع النبات سم،عدد الأفرع ،عدد الأوراق ، المسطح الورقي سم2/النبات ,  وزن المادة الجافة غ/النبات، معدل النمو النسبي ((RGRغ/غ/أسبوع، معدل نمو المحصول ((CGR غ/م2/أسبوع. تفوق التسميد العضوي بالمعدل  30طن/ه (T4) على التسميد الكيميائي(T2) في تقليل عدد الأيام اللازمة للإنبات والنضج التام ،ارتفاع النبات سم، عدد الأوراق/النبات ،مساحة المسطح الورقي سم2/النبات ,  وزن المادة الجافة غ/النبات. أظهرت النتائج عدم وجود فروق معنوية بين المعاملةT4)) والمعاملة T5)) بالنسبة إلى معظم الصفات المدروسة.